2020
DOI: 10.1017/s0954579420000929
|View full text |Cite
|
Sign up to set email alerts
|

Father absence, age at menarche, and genetic confounding: A replication and extension using a polygenic score

Abstract: Father absence has a small but robust association with earlier age at menarche (AAM), likely reflecting both genetic confounding and an environmental influence on life history strategy development. Studies that have attempted to disambiguate genetic versus environmental contributions to this association have shown conflicting findings, though genomic-based studies have begun to establish the role of gene–environment interplay in the father absence/AAM literature. The purpose of this study was to replicate and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 87 publications
(124 reference statements)
0
6
0
Order By: Relevance
“…However, research by Sung et al (2016) who, using a measure of unpredictability that also included residential and employment changes, also did not find an association between unpredictability and AAM. Indeed, a prior study using the ALSPAC data, the focal sample of the current study, did detect the predicted father absence/AAM association (Schlomer & Marceau, 2021). What could account for this difference?…”
Section: Partial Support For Aam and Age At First Sexual Intercourse ...mentioning
confidence: 63%
See 2 more Smart Citations
“…However, research by Sung et al (2016) who, using a measure of unpredictability that also included residential and employment changes, also did not find an association between unpredictability and AAM. Indeed, a prior study using the ALSPAC data, the focal sample of the current study, did detect the predicted father absence/AAM association (Schlomer & Marceau, 2021). What could account for this difference?…”
Section: Partial Support For Aam and Age At First Sexual Intercourse ...mentioning
confidence: 63%
“…By adding many variants of small effect together, PGSs can predict more phenotypic variance than any individual variant on its own. Recent primary and replication research using a PGS consisting of AAM predictive variants (Day et al, 2017) found that the father absence/AAM association could not be explained by genetic variability captured in the PGS (Gaydosh et al, 2018;Schlomer & Marceau, 2021); nor was the association moderated by the PGS, reflecting a lack of GxE (Schlomer & Marceau, 2021). Potential genetic confounding or GxE of harshness and unpredictability associations have not been tested using genomic information in general or the AAM PGS specifically.…”
Section: Addressing Gene-environment Interplay In Research On Harshne...mentioning
confidence: 99%
See 1 more Smart Citation
“…Perhaps it is just that the same genes that affect children's developmental experiences and environmental exposures, including their parenting, also influence pubertal maturation? A number of efforts to at least partially discount this possibility have still found evidence consistent with theoretical expectations upon controlling for maternal age of menarche and GWAS-derived polygenic scores for menarcheal age (D. Gaydosh et al, 2018;Schlomer & Marceau, 2020) and age of first birth (D. . Another strategy that yielded evidence in line with psychosocial acceleration theory used sisters who were full sibs, thus sharing 50% of their genes, finding that, due to a parental breakup, it was younger ones-who spent less time in a fatherpresent family than their older sibs-who sexually matured at a younger age (Tither & Ellis, 2008).…”
Section: The Development Of Reproductive Strategiesmentioning
confidence: 82%
“…Nonetheless, this approach is not as statistically powerful, particularly for detecting main effects, as PGS approaches. It should be noted, however, that relatively few studies to date have incorporated PGS approaches into tests of GxE and there are some possible limitations of this approach for GxE (e.g., Schlomer & Marceau, 2021). Most pertinent to the current study is that it may be difficult to detect disordinal interactions (differential susceptibility) relative to ordinal interactions (diathesis stress) using modern PGS approaches given they emphasize main effect detection (see Zhang & Belsky, 2020).…”
Section: Discussionmentioning
confidence: 99%